IMPLICATIONS OF FEYERABEND’S ANARCHISTIC PHILOSOPHY FOR NIGERIAN EDUCATIONAL POLICIES - Samuel Aloysius Ekanem; Peter Bisong Bisong (Universitas PGRI Madiun, 2021)
Education is a very important variable of economic growth and development. It could be said that the rate of growth of an economy is directly proportional to the quality of education meted on the populace. This is the reason every society strives to educate its citizens. However, Nigeria remains backward in terms of education delivery. There are millions of unemployable graduates rooming her streets searching for jobs. Though many reasons could be pointed as the cause of this, this work beams its searchlight on policymaking and implementation. It argues that if the right policies are made and dutifully implemented, the quality of education would improve. Using the tool of Feyerabend’s anarchism, the work analysed the Nigerian Policy of education, pointing at areas of weaknesses and recommending action points for government and policymakers. It concludes that if Feyerabend’s anarchism is made to guide policy-making in Nigeria, educational progress would ensue.